Voluntary or mandatory training participation as a moderator in the relationship between goal orientations and transfer of training. (3rd October 2016) - Gegenfurtner, Andreas; Könings, Karen D.; Kosmajac, Nikola; Gebhardt, Markus
Abstract : Trainees can participate in organizational training programs voluntarily or mandatorily. To date, research has reported mixed evidence on the question whether voluntary or mandatory participation is associated with higher motivation and transfer of training. Grounded in the frameworks of participatory design, the notion of autonomy in basic psychological needs theory, and the 2 × 2 model of achievement goals, this meta‐analysis examined the relationship between goal orientations and transfer of training in contexts of voluntary and mandatory training participation with a sample of N = 4729 trainees in k = 29 studies. Goal orientations were conceptualized in four dimensions: mastery‐approach, mastery‐avoidance, performance‐approach, and performance‐avoidance. Results of the primary meta‐analysis indicated that mastery‐approach orientation had the most positive correlation with transfer of training, followed by performance‐approach, mastery‐avoidance and performance‐avoidance goal orientation. Meta‐analytic subgroup analysis examined the effects of two conditions for training participation: voluntary participation and mandatory participation. The findings indicated that training participation significantly moderated the correlation coefficients of mastery‐approach and performance‐avoidance goal orientation, with more positive estimates when training enrollment was voluntary. Contrary to expectations, the correlation coefficient between performance‐approach goal orientation and transfer of training was more positive when entry into training programs was obligatory and mandated. Implications for future research and the practice of training design and delivery are discussed.